2017
DOI: 10.1016/j.scriptamat.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Processing effects on fracture toughness of metallic glasses

Abstract: Measuring fracture toughness of metallic glasses (MGs) is challenging, and a large scatter has been observed which has been at least partially attributed to varying processing conditions. Here, we investigated the influence of main processing conditions, cooling rate and processing environment, on the fracture toughness of MGs. Through a thermoplastic forming based toughness evaluation approach, we found that processing effects can be dramatic and typically very specific to the alloy. Hence, general prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The results above clearly show that changing annealing temperature induces changes in the glass microstructure of this model system arising from phase separation and that this compositional segregation correlates strongly with embrittlement. Previous experimental evidence has shown that processing effects such as cooling rate and processing environment also influence the fracture behavior of MGs [28]. Therefore, the observed phase separation may not be the only or even the primary cause of embrittlement arising from changing processing condition.…”
Section: Resultsmentioning
confidence: 95%
“…The results above clearly show that changing annealing temperature induces changes in the glass microstructure of this model system arising from phase separation and that this compositional segregation correlates strongly with embrittlement. Previous experimental evidence has shown that processing effects such as cooling rate and processing environment also influence the fracture behavior of MGs [28]. Therefore, the observed phase separation may not be the only or even the primary cause of embrittlement arising from changing processing condition.…”
Section: Resultsmentioning
confidence: 95%
“…The material prefers to form multiple shear bands rather than shear band delamination, and a higher fracture resistance can be achieved [42,43,51]. The measured fracture toughness is also sensitive to the temperature [108], loading rate, loading mode [107], heat history [109], residual stress [110], geometry [111] and the distribution of impurities/flaws [112]. For example, the cooling rate directly affects the fracture energy of a Ti-Zr-Cu-Ni-Be MG, which can range from 148.9 to only 0.2 kJ m −2 [26].…”
Section: Variability Of Fracture Toughnessmentioning
confidence: 99%